Obvezne sestavine zahtevka za revizijo - Bratina, Tanja (Podjetje in delo, 2014)
The article presents the legislative framework and practical aspects that should be taken into account when filing the request for revision in public procurement procedures. The importance of each mandatory component of the request for revision is highlighted and also the consequence of their absence. Special attention is given to those mandatory components that are crucial to achieve the ruling on merits.
Keywords: javna naročila; pravna ureditev; revizija